2001
DOI: 10.1002/hed.10011
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor ß1 and ß2 (TGFβ2 / TGFβ2) profile changes in previously irradiated free flap beds

Abstract: The radiation induced, increased de novo synthesis of LAP, activation of TGFbeta(1), and increased expression of TGFbeta(2) may represent at least one mechanism for the increased fibrosis and wound healing disorders seen in irradiated tissues and in the transition area to graft tissue. The expression of TGFbeta(1,) LAP, and TGFbeta(2) might possess prognostic value with regard to wound healing and fibrosis in previously irradiated graft beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Such a decrease was also seen during the healing of microvascular soft tissue grafts in the comprised, irradiated graft bed 34 . This expression profiling correlates with the observed regression in the area of peri-implant vessel lumina, which was found to be mainly due to fibrotic rearrangement of the vessel walls 33 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Such a decrease was also seen during the healing of microvascular soft tissue grafts in the comprised, irradiated graft bed 34 . This expression profiling correlates with the observed regression in the area of peri-implant vessel lumina, which was found to be mainly due to fibrotic rearrangement of the vessel walls 33 .…”
Section: Discussionmentioning
confidence: 82%
“…The criteria for a capillary-like structure were a central lumina surrounded by CD105 positively stained cells. To perform exact histomorphometric analysis the area of the capillary lumina as well as the ratio of this area and the area of the total visual field were determined as previously described 32,33 . To quantify the periimplant a-SMA expression the labeling index was determined as the ratio of positively stained cells to the total number of cells per visual field.…”
Section: Qualitative and Quantitative Analysismentioning
confidence: 99%
“…Therefore, a suitable experimental model to study the influences of modulation of TGF--impaired wound healing should include a lack or suprabasal expression of TGF-. The animal model used in this experimental study showed significant activation and de novo synthesis of TGF-1 following irradiation and surgery [32]. It has been shown that total reference doses between 30 and 50 Gy caused lesions in tissues that are comparable to those found in humans after radiotherapy [3].…”
Section: Discussionmentioning
confidence: 77%
“…Pathologic tissue responses may be due to the aberration in the regulation of the TGF-isoforms. Our own in vivo studies showed long-lasting altered suprabasal expression levels of TGF-1 in the irradiated graft bed following free flap transplantation [31,32]. TGF-receptor III (TGF-R-III; endoglin) is expressed predominantly on endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b regulates extracellular matrix remodeling by increasing fibroblast proliferation, differentiation, and activation (Rodemann et al 1991(Rodemann et al , 1996Lara et al 1996;Burger et al 1998;Herskind et al 1998;Hakenjos et al 2000), and thereby increasing secretion of extracellular matrix component proteins (Canney and Dean 1990;VozeninBrotons et al 1999;Schultze-Mosgau et al 2002). TGF-b promotes its own secretion by fibroblasts in a self-amplifying cascade (Burger et al 1998).…”
mentioning
confidence: 96%